Mitotic rate and subcutaneous involvement are prognostic factors for survival after recurrence in patients with only locoregional skin metastasis as the first site of recurrence from cutaneous melanoma. (4th February 2012) - Messeguer, F.; Agustí‐Mejías, A.; Traves, V.; Requena, C.; Alegre, V.; Guillén, C.; Oliver, V.; Nagore, E.
Abstract Background Few reports on literature give detailed figures on prognostic factors of locoregional skin recurrence in cutaneous melanoma. Objective The aim of this study was to evaluate clinical and histological prognostic factors following development of locoregional cutaneous metastasis as the only progression site from melanoma. Methods Data from 1327 stage I and II melanoma patients who visited Instituto Valenciano de Oncología and Consorcio Hospital General Universitario de Valencia from 2000 to 2010 were documented in a prospective manner. During follow up, 112 (8.4%) of them developed recurrent disease. A retrospective analysis revealed a subset of 36 patients with locoregional cutaneous metastases as a first event. Results Significant prognostic factors in the univariate analysis were Breslow thickness, tumor mitotic rate and the presence subcutaneous involvement of the skin metastasis. After multivariate analysis the independent predictive factors for survival after recurrence were tumor mitotic rate (hazard ratio [HR]: 8.6; 95% CI: 1.0–77.2) and subcutaneous involvement of the skin metastasis (HR: 4.3; 95% CI: 1.0–18.5). Conclusion The survival after recurrence of melanoma patients that has relapsed with only locoregional cutaneous metastasis depends on the mitotic rate of the primary tumor and the subcutaneous involvement of the metastasis.